1998
DOI: 10.1056/nejm199806043382307
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Use of Health Care Services

Abstract: Expenditures for health care are similar for male and female subjects after differences in reproductive biology and higher age-specific mortality rates among men have been accounted for.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
113
3
10

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(146 citation statements)
references
References 32 publications
14
113
3
10
Order By: Relevance
“…Persons of all ages made these visits, although the rates of visits were greatest among older ages, paralleling previous data for arthritis prevalence (1-3,16). Women had almost twice as many arthritis visits as men across combined settings, which is consistent with their higher prevalence of arthritis, their perceived lower health-related quality of life and physical functioning, and their higher medical care service utilization (2,3,(17)(18)(19)(20). All races used all settings, although rates were lower for "other" races.…”
mentioning
confidence: 53%
“…Persons of all ages made these visits, although the rates of visits were greatest among older ages, paralleling previous data for arthritis prevalence (1-3,16). Women had almost twice as many arthritis visits as men across combined settings, which is consistent with their higher prevalence of arthritis, their perceived lower health-related quality of life and physical functioning, and their higher medical care service utilization (2,3,(17)(18)(19)(20). All races used all settings, although rates were lower for "other" races.…”
mentioning
confidence: 53%
“…women visit physicians more than men do [1,3,7,8] and use other diagnostic services (e.g. laboratory tests, blood pressure checks, prescriptions) more than men.…”
mentioning
confidence: 99%
“…Many researchers have shown that the F/M ratio for prescription drug use is highest in younger women and decreases in older age groups. [4,7] This chapter looks at the extent to which social roles (being a parent, spouse, worker) and demographic and other risk factors are associated with medication use, categorized as prescription (Rx) and over-the-counter (OTC) medication use, in adults aged 20 years and older. For the main analyses hormone use was excluded as it is known that women have higher use of hormones.…”
mentioning
confidence: 99%
“…Women have similar or slightly lower rates than men for life-threatening chronic conditions, such as coronary heart disease and cancer. [1,3,7,[13][14][15][16] The higher prevalence of disability, another key measure of population health, among women as compared with men is also fairly well established, [3,9,[17][18][19] and is at least in part accounted for by the higher prevalence of disabling chronic conditions, such as arthritis, among women. [3,20] Various measures of disability, such as activity limitation and dependence on others for daily tasks, and composite measures, such as the Health Utility Index, [21][22][23] have been used to compare the functional status of various populations.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30] After adjustment for sexspecific diagnosis and higher mortality rates among men, hospital services were found to be comparable between men and women. [18] However, lower levels of morbidity were found among employed women as compared with homemakers, particularly among women working part time. [19] A higher prevalence of activity limitation was also found in groups with lower educational attainment and income, [10,12,17,30,31] although these differences were weaker for education.…”
Section: Introductionmentioning
confidence: 99%